Hubungan Jenis Dan Tipe Rumah Sakit Dengan Pengetahuan Perawat Anak Mengenai Luka Tekan - Sari, Dian (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: To identify the relationship between the type and class of hospital with pediatric nurses' knowledge of pressure ulcers in South Sumatera Province Method: This study used a cross-sectional design with a convenience sampling method on 149 pediatric nurses in South Sumatera Province. Data collection was carried out in September 2023 to August 2024. Mann-Whitney and Kruskal-Wallis tests to examine the relationship between the type and class of hospital and knowledge of pediatric nurses regarding pressure ulcer. Results: The Mann-Whitney test showed no relationship between the type of hospital and pediatric nurses' knowledge of pressure ulcers (p> 0.05), while the Kruskal Wallis test showed a relationship between the class of hospital and pediatric nurses' knowledge of pressure ulcers (p < 0.05). Conclusion: There is no relationship between the type of hospital and pediatric nurses' knowledge of pressure ulcers and there is a relationship between class of hospital and pediatric nurses' knowledge of pressure ulcers